2013
DOI: 10.1103/physrevb.88.045432
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dopants on the band structure of quantum dots: A theoretical and experimental study

Abstract: In this article, we present a theoretical framework that provides predictable results on band gap modifications due to the addition of dopants into CdSe quantum dots (QDs). A theoretical model is developed that predicts a lowering of the conduction band minimum (CBM) due to hybridization. We then use x-ray absorption spectroscopy (XAS) at the Cd M3-edge to determine the effects of chemical doping on the CB of the QD. Analysis of the XAS onset energy provides evidence for a lowering of the CBM, with our calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 22 publications
2
15
1
Order By: Relevance
“…22 Meulenberg et al have shown in the past few years that increasing the amount of Cu(I)-dopant ions in the host CdSe CQDs affects the lowest empty electronic states (CB) in a way inconsistent with the quantum confinement (QC) theory. 40 Concisely, increasing Cu(I)dopant ions in CdSe CQDs results in the decrease of CB edge (only), which further shifts the PL emission spectrum to longer wavelengths. Meulenberg et al have explained these results as a result of the hybridization of CdSe orbitals by successful substitution of Cu(I) ions in the CdSe host medium proved this hypothesis through theoretical modeling, X-ray absorption (XAS) spectroscopy 40 and, more recently, ultraviolet photoemission spectroscopy (UPS).…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Meulenberg et al have shown in the past few years that increasing the amount of Cu(I)-dopant ions in the host CdSe CQDs affects the lowest empty electronic states (CB) in a way inconsistent with the quantum confinement (QC) theory. 40 Concisely, increasing Cu(I)dopant ions in CdSe CQDs results in the decrease of CB edge (only), which further shifts the PL emission spectrum to longer wavelengths. Meulenberg et al have explained these results as a result of the hybridization of CdSe orbitals by successful substitution of Cu(I) ions in the CdSe host medium proved this hypothesis through theoretical modeling, X-ray absorption (XAS) spectroscopy 40 and, more recently, ultraviolet photoemission spectroscopy (UPS).…”
Section: ■ Discussionmentioning
confidence: 99%
“…40 Concisely, increasing Cu(I)dopant ions in CdSe CQDs results in the decrease of CB edge (only), which further shifts the PL emission spectrum to longer wavelengths. Meulenberg et al have explained these results as a result of the hybridization of CdSe orbitals by successful substitution of Cu(I) ions in the CdSe host medium proved this hypothesis through theoretical modeling, X-ray absorption (XAS) spectroscopy 40 and, more recently, ultraviolet photoemission spectroscopy (UPS). 22 However, presence of these electronically and optically active states below the CB due to Cu(I) doping and redshifting of emission spectra by increasing the number of dopant ions in the host lattice can be confused with the particle size distribution inherent within the ensemble of doped CdSe CQDs.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Therefore, the recombination of delocalized conduction band (CB) electrons with strongly localized holes in Cu-/Ag-doped CQDs results in a broad and Stokes-shifted dopant-induced emission. The tunability of the dopant-induced emission for Cu-/Ag-doped CQDs is realized by changing the NC particle size or by alloying the semiconductor NC [86], [87]. Both the techniques result in a shift of the CB level, which in turn tunes the emission spectrum.…”
Section: A Doping Of Cdse Npls By the High-temperature-based Nucleatmentioning
confidence: 99%
“…orbital hybridization of host CdSe orbitals. With the aim of controlling individual CB/VB levels with respect to the cathode/anode, Wright and Meulenberg [87] and Wright et al [91]showed that an increase in Cu(I) substitutional doping of host CdSe CQDs affects the lowest CB level in a way inconsistent with a quantum confinement theory. An increase in the Cu(I) doping levels in the host CdSe results in a decrease in the CB edge (only).…”
Section: (A) Copper Doping Procedures Through the Partial Ce Reactiomentioning
confidence: 99%
“…In addition, Cd M 3 -edge XANES spectra (Fig. 2), an edge whose nal state is directly probing the conduction band minimum, 22,23 displays a shi of the absorption edge with decreasing particle size. This result is consistent with quantum connement effects.…”
Section: Surface Structure Of the Quantum Dotsmentioning
confidence: 99%